Strategy implementation in private equity funded companies - Henriksson, Anders (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2023)
Research exploring strategy implementation in the context of private equity funded companies is sparse. Addressing this gap, this study has inquired into the cooperation between the key stakeholders of a recently acquired portfolio company and the acquiring private equity firm during the portfolio company’s four-year holding period. The research is grounded in the Strategy as Practice (SAP) paradigm and utilizes an insider action research method. By using this approach, it was possible to uncover unique insights on micro-level processes and action as well as rich narratives. From this data, an empirically grounded and explanatory strategy implementation framework was developed. This contains three dimensions including a Strategy Process Dimension, a Leadership Dimension, and a Value Creation & Growth Dimension with distinct phases and structural elements. Additionally, 8 novel research propositions could be identified. This study is a rare attempt to immerse into a private equity context. Based on for the context novel participatory approaches, important contributions to strategy implementation research are made (including in terms of approach) and additionally contributions to the SAP and buy-out literatures are made.